India's aged : needs and vulnerabilities - Mishra, U. S. (Udaya Shankar), 1965-; Irudaya Rajan, S. (Sebastian), 1959- (Orient BlackSwan, 2017)
India’s Aged: Needs and Vulnerabilities discusses the most vulnerable aspects of elderly life—health and well-being—under the current conditions of economic and societal change. This volume explores (a) whether the nature of living arrangements has a bearing on the health outcomes of the elderly; (b) whether the real or perceived economic dependence and financial vulnerability of the elderly is conditioned by translation of capabilities into functioning; and (c) the implied healthcare costs, which are defined as based on both actual needs and the elderly people’s own perception of their needs. Living arrangements have to be linked with the health and well-being of the elderly, given the absence of universal social security, an inadequate formal system of care, as well as the gradual erosion of the joint family system. While it is obvious that rising healthcare costs are a reality due to rising longevity, this volume shows how population ageing contributes to rising healthcare costs, along with projected healthcare costs in the future. In addition, this volume addresses issues such as access to finance, financial autonomy and financial inclusion of the elderly. Bringing together empirical explorations of prevailing realities and mechanisms that shape the well-being/ill-being of the elderly in India, this volume will be indispensible for students and scholars of economics, development studies, and health and wellness studies.